Development and Synchrotron‐Based Characterization of Al and Cr Nanostructures as Potential Calibration Samples for 3D Analytical Techniques (Phys. Status Solidi A 6∕2018). Issue 6 (25th March 2018) - Dialameh, Masoud; Ferrarese Lupi, Federico; Hönicke, Philipp; Kayser, Yves; Beckhoff, Burkhard; Weimann, Thomas; Fleischmann, Claudia; Vandervorst, Wilfried; Dubček, Pavo; Pivac, Branko; Perego, Michele; Seguini, Gabriele; et al.
Abstract : Large‐scale sub‐20 nm regular pattern obtained by self‐assembly of di‐block copolymers. The combination of reference free grazing incidence X‐ray fluorescence (GIXRF) and GIXAS techniques enables a complete characterization of such a 3D system and provides a potential calibration sample for 3D analytical techniques. This is reported by Masoud Dialameh and co‐workers in article1700866 .